Prevalence and specific features of metabolic syndrome in urban adult population - Z. N. Tokareva; M. N. Mamedov; A. D. Deev; A. A. Evdokimova; R. G. Oganov (Кардиоваскулярная терапия и профилактика, 2010)
Aim. To study the prevalence and specific clinical features of metabolic syndrome (MS) in a random sample of urban adult population. Material and methods. In total, 1800 participants were randomly selected: 749 men and 1051 women, aged 30-69 years. The study protocol was completed by 1570 subjects: 620 men and 950 women (response rate 87,2%). All participants underwent standard questionnaire survey, anthropometry, and the measurement of blood pressure (BP), blood lipids, and blood glucose (fasting glycemia and glycemia at 2 hours after oral glucose tolerance test). Results. According to the NCEP ATP III criteria, MS was registered in 314 participants (20,6%), and according to the IDF criteria – in 447 (28,5%; p<0,0001). On average, MS was twice as prevalent in women as in men. In both genders, advanced age was associated with increasing MS prevalence. The majority of the participants had three MS components (61,5%). Four MS components were registered in 28,7%, and all the components were observed in 9,8%. The most prevalent MS component was low level of high-density lipoprotein cholesterol (68,8%), followed by hypertriglyceridemia (65,3%), abdominal obesity by ATP III criteria (65%), arterial hypertension, AH (65%), and hyperglycemia (45,2%). Each third respondent with MS demonstrated clinical manifestations of atherosclerosis, such as coronary heart disease, myocardial infarction in anamnesis, peripheral or cerebrovascular atherosclerosis. Conclusion. Among this working-age population, MS prevalence was 20%. The most common MS components included dyslipidemia, AH, and abdominal obesity. Each third MS patient had various manifestations of cardiovascular pathology.